PENGGUNAAN PENDEKATAN BERMAIN UNTUK MENINGKATKAN KETERAMPILAN GERAK DASAR LEMPAR TANGKAP DALAM PEMBELAJARAN PERMAINAN KASTI - ARYANTI ARIFIN, FENI (2014)
The arising problems of the physical education learning in the field were the lack of the students' basic movement skills in throwing and catching. The formulation of problem in this study was whether the playing approach could improve the basic movement skills of throwing and catching in kasti game learning on the students at the fourth grade of SD Negeri Kadipaten VII. The aim of the research was to know the improvement of the basic movement skills of throwing and catching on the students at the fourth grade of SD Negeri Kadipaten VII by holding playing approach in kasti game learning. The method used in this study was classroom action research or penelitian tindakan kelas on the students at the A fourth grade of SD Negeri Kadipaten VII Majalengka regency totally 34 students. The instrument used in this study was the assessment format of the basic movement skills of throwing and catching (psychomotor skills), field record sheet and documentation. the action implementation began by the first observation. the next step was to create an action planning that consisting of two cycles with each cycle consisting of two actions. Improved the average percentage of the students who carried out the basic movement of throwing and catching at the beginning test achieved 41.07%, in the first cycle, the first action achieved 48.63%, and the second action achieved 62.55%, while in the second cycles, the first action achieved 74.00%, and the second action achieved 81.03%. These results indicated that by applying the playing approach, then the basic movement skills of throwing and catching on the students could be improved, and the students' understanding in physical education learning especially the kasti game could be better and improved.